2022
DOI: 10.1186/s13063-022-06605-1
|View full text |Cite
|
Sign up to set email alerts
|

Fostering shared decision-making about prostate cancer screening among African American men patients and their primary care providers: a randomized behavioral clinical trial

Abstract: Background Prostate cancer is the third most prevalent cancer in the American population. Furthermore, the prognosis is worse in African American as there is increased morbidity and mortality associated with it. Purpose The purpose of this study is to evaluate the effectiveness of a new online method to educate the patient population regarding prostate cancer risk, diagnosis, treatments, and their decisions about whether to be screened for the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Carlson et al demonstrated that education at the time of prostate cancer screening in the setting of outreach events increases patient knowledge and additional randomized trials are underway. [42][43][44] Targeted community outreach programs such as barbershop engagement programs are feasible among Black patients 45 ; similar creative interventions informed by cultural humility should be explored in other minority groups including Hispanic men. In the more advanced disease states, interventional studies are sorely needed.…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al demonstrated that education at the time of prostate cancer screening in the setting of outreach events increases patient knowledge and additional randomized trials are underway. [42][43][44] Targeted community outreach programs such as barbershop engagement programs are feasible among Black patients 45 ; similar creative interventions informed by cultural humility should be explored in other minority groups including Hispanic men. In the more advanced disease states, interventional studies are sorely needed.…”
Section: Discussionmentioning
confidence: 99%
“…A currently accruing trial of Black men undergoing PSA screening employs an online decision aid and evaluates outcomes including patient engagement scores, prostate cancer knowledge, and decisional confidence, self-efficacy, and satisfaction. 3 These studies offer tools to augment men’s understanding of their prostate health, and may mitigate the time pressures of a busy clinical practice while achieving health equity. Further, decision aids should be culturally tailored to minority men, especially those who are non-English speaking.…”
mentioning
confidence: 99%